Indices of the Hierarchical Structure of Industrial Organizations - Evan, William M. (Management Science, 1963)
A postulate common to both the structural-functional theory of social stratification and to organization theory is that hierarchical organization is functionally necessary. An alternative formulation of this postulate—which is probably more heuristic—is that different degrees of hierarchical organization have different consequences for total and partial social systems. The present inquiry into the problem of measuring organizational hierarchy begins with the selection of three central dimensions of organization: the hierarchy of skills, the hierarchy of rewards, and the hierarchy of authority. For each dimension an attempt is then made to develop and codify one or more indicators. The question of the empirical application of the indicators of the hierarchical dimensions in turn leads to a consideration of the problems of index construction, analysis of change over time, analysis of causes and consequences of variation in degree of organizational hierarchy, and of comparative research, whether cross-national, cross-organizational, or experimental in character.